1995
DOI: 10.1002/j.1552-4604.1995.tb05022.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressor Effect of Oral Tyramine During Treatment with Befloxatone, a New Reversible Monoamine Oxidase‐A Inhibitor, in Healthy Subjects

Abstract: The interaction between tyramine and befloxatone, a new selective, reversible monoamine oxidase-A (MAO-A) inhibitor, was studied in a single-blind, parallel-group study in 30 healthy male volunteers whose fasting tyramine 30 dose (Tyr30) was 400 or 600 mg. Each subject completed a placebo run-in period followed by a befloxatone period. Befloxatone was given in repeated doses according to one of three regimens: befloxatone 20 mg once daily at the end of a meal rich in tyramine or befloxatone 10 or 20 mg twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Cimoxatone was never registered for the market as it caused a tyramine pressure response comparable to the irreversible inhibitor clorgyline (Emilien, 1999). Befloxatone (Consonar, MD370, 503), another MAO-A selective inhibitor of the same class with a high affinity for MAO-A (2 nM), was developed in the 1990s for the treatment of depression by Synthelabo (France) (Patat et al, 1995;Curet, 1996).…”
Section: Reversible Selective Mao-a Inhibitors (Rima)mentioning
confidence: 99%
“…Cimoxatone was never registered for the market as it caused a tyramine pressure response comparable to the irreversible inhibitor clorgyline (Emilien, 1999). Befloxatone (Consonar, MD370, 503), another MAO-A selective inhibitor of the same class with a high affinity for MAO-A (2 nM), was developed in the 1990s for the treatment of depression by Synthelabo (France) (Patat et al, 1995;Curet, 1996).…”
Section: Reversible Selective Mao-a Inhibitors (Rima)mentioning
confidence: 99%
“…Indeed, it has been reported that increasing mainly lipid but also protein content of the meal significantly reduce the tyramine blood pressor response (Audebert et al, 1992). Bioavailability of tyramine when administered with food or as a dietary constituent seems to drastically be reduced and systematic concentrations are reduced by approximately 2-to 3-fold (Patat et al, 1995;Van den Berg et al, 2003;Azzaro et al, 2006).…”
Section: Dose-response Relationshipmentioning
confidence: 99%
“…The results from literature showed that from 600 mg up to 2,000 mg of tyramine administrated in a meal would be needed to cause a minimal systolic blood pressure increase (of at least 30 mmHg). Therefore the intestinal barriers to tyramine in non-medicated healthy volunteers (placebo groups) seem to be effective to avoid tyramine intoxication from food (Korn et al, 1988a;Berlin et al, 1989;Zimmer et al, 1990;Patat et al, 1995). A doseresponse curve was generated by Patat et al (1995), in which 1100 mg of tyramine correspond to the effective dose (ED 50 ) as the tyramine dose at which 50% of the individuals responded.…”
Section: Dose-response Relationshipmentioning
confidence: 99%
See 2 more Smart Citations